RSVP X: Anamnesis, 2005 [poster] (2005)
Poster reads: 'Concert celebrating electro-acoustic diversity and compositional risk. RSVP X: Anamnesis. an-am-ne-sis: a recollection; recalling to memory. Showing May 31, June 2, Cal Poly Performing Arts Center. Tickets $10 each at the PAC Ticket Booth. www.pacslo.org, 1.888.233.ARTS. Sponsored by the College of Liberal Arts and the Music Department of Cal Poly.'